To study the outcomes of scrotal exploration for acute scrotal pain in relation to monthly and daily temperature variations: A large contemporary series from a Teaching Hospital - Adeel Anwar; Ghulam Mustafa Nandwani; Sanjai K Addla; James A Forster (Journal of University Medical & Dental College, 2024)
ABSTRACT:            BACKGROUND & OBJECTIVE:Acute testicular pain requires emergency exploration for suspected testicular torsion (TT). It has been suggested that temperature variation is associated with TT. However, it was not possible to conclude whether the higher occurrence of TT was related to TT itself or the effect of the overall higher presentation of acute scrotum. We studied the impact of seasonal and daily temperature variations on acute testicular pain and outcomes.METHODOLOGY: Retrospective data collection on patients required testicular exploration between January 2006 and December 2017 for TT. The Kruskal Wallis test & chi-square tests were used to assess the group difference between continuous and categorical variables, respectively.RESULTS: In total, 502 patients required testicular exploration. The median age and duration of symptoms were 16.4 yrs. (1.3 – 77) and 4 hrs. (1 – 336). Respectively, TT was found in 231 (46%), torsion of the testicular appendix (TTA) in 126 (25%), epididymal inflammation (EI) in 46 (9.2%), and no identifiable cause (NIC) was found in 99 (19.7%). Scrotal explorations were more common in groups with mean daily temperature >6.20C, 60.2% Vs 39.8% while there was no difference in TT 46% Vs 46% in these groups.CONCLUSION: There was no seasonal variation for testicular torsion or operative findings. Cold weather and average low daily temperatures were not related to testicular torsion.